2020
DOI: 10.1002/hyp.13613
|View full text |Cite
|
Sign up to set email alerts
|

Application of GRACE to the estimation of groundwater storage change in a data‐poor region: A case study of Ngadda catchment in the Lake Chad Basin

Abstract: The present study is to explore the feasibility of GRACE-based estimation of a groundwater storage change in a data-poor region using a case study of the Ngadda catchment in the Lake Chad Basin. Although the Ngadda catchment has only one set of in situ time series data of groundwater from 2006 to 2009 and a limited number of groundwater measurements in 2005 and 2009, GRACE-based groundwater storage change can be evaluated against the in situ groundwater measurements combined with specific yield data. The cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 77 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…This implies that the coarse spatial resolution of GRACE is problematic for monitoring groundwater resources for small areas. A recent study by Skaskevych et al [86] assessed the feasibility of GRACE-based estimation of groundwater storage change in the Ngadda catchment in the Lake Chad Basin and demonstrated that GRACE-based modelling is a cost-effective method to monitor groundwater changes. While important insights have been gained from using this sensor, the coarse resolution limits its application over finer spatial scales.…”
Section: Remote Sensing Products For Drought and Climate Variability mentioning
confidence: 99%
“…This implies that the coarse spatial resolution of GRACE is problematic for monitoring groundwater resources for small areas. A recent study by Skaskevych et al [86] assessed the feasibility of GRACE-based estimation of groundwater storage change in the Ngadda catchment in the Lake Chad Basin and demonstrated that GRACE-based modelling is a cost-effective method to monitor groundwater changes. While important insights have been gained from using this sensor, the coarse resolution limits its application over finer spatial scales.…”
Section: Remote Sensing Products For Drought and Climate Variability mentioning
confidence: 99%
“…Lake Chad (LC), which was once the third-largest source of fresh water in Africa, has tremendously decreased in size, endangering the livelihoods of approximately 30 million people who rely on the lake. Agriculture, nomadic and semi-nomadic animal husbandry and fisheries are the predominant sources of income around LC [3,4]. Given such importance within the community, the routine monitoring of water quality is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Given such importance within the community, the routine monitoring of water quality is essential. Unfortunately, monitoring records are lacking due to limited financial and infrastructural investments [4,5]. The possible challenges in measuring and monitoring water quality in situ for such a large area include spatial constraints, high costs, and the significant time required.…”
Section: Introductionmentioning
confidence: 99%
“…These scenarios were defined based on observations reported in previous studies. For example, estimation of groundwater storage change based on in situ and remotely sensed groundwater data in the Lake Chad Basin indicated that the groundwater water storage could decrease to half of its value and even to zero due to both climate change and overexploitation of water (Skaskevych et al., 2020).…”
Section: Introductionmentioning
confidence: 99%